The effect of menstrual cycle phase on recovery after exercise - A review on recovery after endurance and resistance exercise among eumenorrheic women - Asp, E. E.; Hoffmann, E. G. (NTNU, 2023)
Purpose: To this day there is a lack of sport and exercise science research including female athletes. Therefore, it is relevant to research the influence the menstrual cycle (MC) has on sport and exercise. The aim of this literature review is to assess the effect the MC has on recovery after exercise.